ศึกษาความสัมพันธ์ของการอ้างอิงหะดีษเมาฎูอฺกับการอ่านคุตบะฮฺนิกาห์ในพิธีการแต่งงาน กรณีศึกษา: การปฏิบัติของมัสญิด ในตำบลไม้ขาว จังหวัดภูเก็ต - หมัดตะพงศ์ นัศรุลลอฮ์; การีนา อับดุลเลาะ (Al-HIKMAH Journal, 2018)
This paper aims to study a relationship between the reference of al-Hadith al-Maudhu’ and the kuthbah nikah sermon in Musjids in Maikaw District, Phuket Province. It employs a qualitative methodology, collects data by using questionnaire and interview, and analyzes the data by resorting to the principle of Hadith Science, Islamic Jurisprudence, and Tarjih. The findings show that Hadith Maudhu’ has been used in the kuthbah nikah sermon, but, according to the principle of Hadith Science, this kind of Hadith cannot be considered as valid. There are five Hadiths as follows 1) Hadith that encourages and discourage a marriage with a woman because of some qualifications; 2) Hadith that encourages choosing a partner who has a good linage because a good linage can be transferred to a child 3) Hadith that prohibits a marriage with a close relative because doing so will make a child having a defect 4) Hadith that mentions that the Ibadah or prayer of a married person is more blessing than a non-married one; and 5) Hadith that mentions that a divorce is an unpleasable act and, as a consequence, it shakes the throne of Allah